The Concept of ‘Construction’ and the Practice of Linguistic Analysis in First Language Teaching: Potentialities and Challenges Focusing on the use (Revista de Estudos da Linguagem, 2024)
The goal of this paper is to propose an argumentative rationale about the intersection of the concept of ‘construction’, proposed by Cognitive Grammar, with the practice of linguistic analysis in first language classes, aligned to a usage-based approach. To do so, a brief review of the concepts relevant to the proposed dialogue is presented and the analysis of a special case is developed. During the analysis, constructions with verbs of movement (ir ‘to go’, vir ‘to come’ and chegar ‘to arrive’) followed by the prepositions a ‘at’, em ‘in’ and para ‘to’ were identified and descripted in the TecEM corpus, composed of texts written by high school students in their Portuguese language classes. It is argued that the concept of ‘construction’ in LC informs and instrumentalizes the practice of linguistic analysis in first language classes, based on the understanding that the meaning goes beyond the level of the lexical item, being in the syntactic structure as well. Finally, the potentialities and challenges associated with the inclusion of the concept of ‘construction’, associated with the fundamental theoretical constructs of Cognitive Linguistics, in didactic practices in first language teaching are highlighted.